Postgraduate students’ experience with Zoom-based learning: focus on affordability, access, teaching quality, and assessment - Nawastheen, Fareed Mohamed; Ketheeswaran, Kanapathippillai; Perera, S.A.S. Kausalya; Shifaan, Shajehan (Penerbit Universiti Kebangsaan Malaysia, 2024)
With the COVID-19 pandemic in 2020, Sri Lankan universities turned to video conferencing to maintain academic activities, with Zoom being a popular choice. This study explores postgraduate students' experiences in two Master of Education (M.Ed.) programmes at a Sri Lankan university regarding Zoom-based online learning. It investigates student perceptions across four key areas: affordability, access and instructor support, quality of teaching, and effectiveness and fairness of assessments. A survey approach was used, with a researcher-developed questionnaire administered online to 189 students studying Sinhala, Tamil, and English. The questionnaire included close-ended questions, Likert-scale items, and open-ended questions, with data analyzed using descriptive statistics. Findings indicate that students generally found Zoom-based instruction accessible and effective. However, areas for improvement were identified, such as enhanced instructor support, a more interactive learning environment, and comprehensive course coverage. Concerns also emerged about instructor support during assessments, clarity of formats, and time allocation. Qualitative data highlighted issues with session length, technology affordability, and a preference for diverse assessment methods. The study provides insights for enhancing M.Ed. programmes conducted online. Recommendations include faculty capacity development in online teaching, promoting the affordability of Zoom-based learning, and refining assessment practices. Addressing these areas and seeking student feedback can help institutions create high-quality, engaging, accessible, and effective Zoom-based programmes.